2013
DOI: 10.1093/icvts/ivt217
|View full text |Cite
|
Sign up to set email alerts
|

The role of surgical lung biopsy in the management of interstitial lung disease: experience from a single institution in the UK

Abstract: SLB is a well-recognized procedure. Although it provides a diagnosis for the majority of patients, in our series SLB was inconclusive in a considerable number of cases and did not lead to a therapeutic change for more than half of all patients. Furthermore, SLB is not without risk and can be associated with a prolonged hospital stay. We believe that SLB should be performed in a select group of patients with ILD after discussion by a multidisciplinary panel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
55
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 18 publications
6
55
2
1
Order By: Relevance
“…Granulomatous diseases have been reported in 5 to 16% and malignancy in 5 to 13.3% of patients. [5][6][7]18,20,21] In the published series, the diagnostic yield of SLB ranged between 34 to 98% and the most common diagnosis was reported as IPF. [19,20] In the current study, final diagnosis was reached in 80% and the most common diagnosis was UIP, which complies with the existing literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Granulomatous diseases have been reported in 5 to 16% and malignancy in 5 to 13.3% of patients. [5][6][7]18,20,21] In the published series, the diagnostic yield of SLB ranged between 34 to 98% and the most common diagnosis was reported as IPF. [19,20] In the current study, final diagnosis was reached in 80% and the most common diagnosis was UIP, which complies with the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, taking multiple biopsies have been suggested in the first published reports and in current guidelines. [3,4,22] In 2013, Blackhall et al [6] reported that a median of two biopsies significantly increases the probability of reaching a definitive diagnosis. On the other hand, sampling from either a single biopsy or multiple biopsies have not made a significant difference in providing a diagnosis in other reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…52 Two studies reported yields below 70%, although these outliers were limited by the lack of SLBx review in a MDD. 53,54 The yield of SLBx can be optimized through several means. 3 Biopsies should have a depth 2 cm and maximum diameter 4 cm when gently inflated post-resection.…”
Section: Surgical Lung Biopsymentioning
confidence: 99%